A relação família-escola: fronteiras e possibilidades - CRUZ, Fatima Maria Leite (2012)
O artigo aborda a problemática da relação família-escola na contemporaneidade, analisando os vários fatores de ambigüidade e de fragilidade segundo a perspectiva psicossocial, que serviu de ancoragem teórico-metodológica às pesquisas que embasaram as investigações e proposições lançadas. É apresentado o cenário social das mudanças que alicerçam a relação, tanto na ordem econômica quanto nos valores que a circundam; faz-se uma retrospectiva histórica das duas instituições educativas; e em seguida, uma abordagem sobre alguns dos principais aspectos que provocam impasses e limites na relação, assim como são lançadas possibilidades de superação.Family-school relationship: limitations and possibilitiesAbstractThis study focuses on the current problem faced in the family-school relationship. Various factors related to ambiguity and to fragilities were analyzed from the psychosocial perspective in which the research was in theory and in method established, and on which the investigations and the proposals were based. The economical changes and the changes on the basic values of the very elementary relationship are presented inserted into a social scenario. A historical background from the two educational institutions is presented, followed by a projection about some of the most important aspects which introduce issues and limitations into the relationship, and make motivational proposals.Keywords: School. Family. Interaction.